2019
DOI: 10.5812/archcid.85766
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Genes Involved in Biofilm Formation in MDR and XDR Acinetobacter baumannii Isolated from Human Clinical Specimens in Isfahan, Iran

Abstract: Background: Acinetobacter baumannii is capable of forming biofilms that may be responsible for the survival of this pathogen in the hospital environment as well as antibiotic resistance. Objectives: In this study, considering the importance of genes bap, blaPER-1, and csuE in the formation of biofilms and resistance to antimicrobial drugs, we aimed to investigate the frequency of these genes and also the relationship between these genes and the biofilm formation. Methods: One hundred and eighteen clinical stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
4
9
0
Order By: Relevance
“…The results of our study show that all A. baumannii isolates carried the bap gene, which makes this gene useful as one of the markers of A. baumannii infections. Our findings are similar to the results obtained by Monfared et al [ 34 ]. They have also shown that the bacteria lacking the bap gene are incapable of biofilm synthesis.…”
Section: Discussionsupporting
confidence: 94%
“…The results of our study show that all A. baumannii isolates carried the bap gene, which makes this gene useful as one of the markers of A. baumannii infections. Our findings are similar to the results obtained by Monfared et al [ 34 ]. They have also shown that the bacteria lacking the bap gene are incapable of biofilm synthesis.…”
Section: Discussionsupporting
confidence: 94%
“…The objective of our study was to demonstrate a new approach for using the bacteriophage to treat life-threatening MDR A. baumannii infections. The antibiotic sensitivity of 48 A. baumannii isolates revealed that the prevalence of MDR and pan-drug A. baumannii is increasing in the region, which is in agreement with other studies in different countries [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study in Isfahan, Iran, 16.1% of 118 isolates of A. baumannii were XDR. In another study in Zanjan, Iran, Zighami et al reported that 91% of A. baumannii isolates were XDR, 9,28 indicating different frequencies in various geographical regions of the country. In our study, since the sample size was relatively small, non‐biofilm producer isolates were not found, and this limitation should be considered in future studies in the region.…”
Section: Discussionmentioning
confidence: 99%